Mechanical characterization of composites polyester moulding reinforced waste metal lathes with standard ASTM D 638-lll modification - Idris, Iswandi; Aditya Sari, Ruri; ., Hendriko; Novia Syamsir, Hendri (International Journal of Engineering and Technology, 2018)
Scope and Objectives of this research are: To improve the mechanical characteristics of polyester composite fabricated waste metal lathe and Styrofoam through tensile test, compression test, impact test, obtain a new note for developing new composite materials by use waste metal lathe and plastic waste Styrofoam in order not to waste. from the test results obtained tensile strength 0.66 kg f/ mm2, greatest moment 5,490 kg f.m, greatest stress 1.93 kg f/ mm2, strain 0.17093 m/m and bending angle 167.64. The breakpoints of the composite specimen in which the waste lathe located is at 0.65, the elastic behaviour seen from the number 0 to the 1.06 proportional limit, then at the voltage level 1.1 of the plastic behaviour and the 1.633 level has undergone plastic deformation until the breakpoints.The charphy impact implies 110 (J / mm 2). From the experimental results showed that the composite fabric waste has good mechanical properties.Â Â